A Molecular Imprinted Polymer Sensor for Biomonitoring of Fenamiphos Pesticide Metabolite Fenamiphos Sulfoxide. Issue 5 (16th March 2021) - Qader, Bakhtiyar; Hussain, Issam; Baron, Mark; Jimenez‐Perez, Rebeca; Gonzalez‐Rodriguez, Jose; Gil‐Ramírez, Guzmán
Abstract: A new electrochemical method for the identification and quantification of Fenamiphos pesticide's major metabolite in biological samples – Fenamiphos Sulphoxide (FNX ) was developed. Computational calculations, Density Functional Theory (DFT) and semi‐empirical models (PM3) were performed to determine the best monomer, pyrrole, and a ratio of 1 : 5 (template: monomer) was chosen for the fabrication of the FNX− MIP sensor obtained by electropolymerization. The FNX− MIP sensor responded well to increasing FNX concentrations (range of 1–30 μM). Limit of detection and quantification (LOD=0.183 μM, LOQ=0.601 μM), respectively, selectivity, and repeatability were also investigated for the developed method. The obtained percentage of recovery showed good agreement compared to reference values obtained from GC‐MS, which was used as a reference method. The FXN− MIP sensor proved selective in the presence of potential interferents. The developed sensor was successfully applied for the determination of FNX in spiked plasma and urine matrixes with acceptable recovery rates. The proposed method also proved successful in detecting FNX prepared from the in vitro metabolism of FNP using liver microsomes to metabolize it. Abstract :